Pengaruh Reputasi Auditor, Prediksi Kebangkrutan, Disclosure Dan Leverage Terhadap Penerimaan Opini Audit Going Concern - Eko Budi Santoso; Ivan Yudhistira Wiyono (AKRUAL: JURNAL AKUNTANSI, 2013)
AbstractGoing concern opinion is accepted by a company represents the condition and events which arises auditors hesitation of the companys going concern. Going concern audit opinion used as early warning to the user of financial statements in order to prevent mistakes on decision making. This study objective was to reinvestigate factors that influencing going concern audit opinion. The factors used on this research are auditor reputation, bankruptcy prediction, disclosure and leverage.Samples were collected with purposive sampling method and obtained 229 observation data of listed manufacture companies that meet the criteria from year 2009-2011. Logistic regression was been used for hypothesis testing. The result showed that bankruptcy prediction using Z-score model and leverage affected acceptance going concern audit opinion. The hypothesis testing also showed that auditor reputation and disclosure did not affect acceptance going concern audit opinion.